Weak rock mass characterization for determination of support system of the DK99-DK100 Jakarta – Bandung speed railway tunnel, Indonesia. Issue 1 (October 2021) - Ali, L; Indrawan, I G B; Hendarto,
Abstract: Rock mass characterization is a crucial factor in determining a safe design of a tunnel support system. This research is carried out in constructing tunnel DK 99 – DK 100 high-speed railway Jakarta-Bandung, Indonesia. The research includes determining surface and subsurface quality of rock masses based on rock mass classifications of Geological Strength Index (GSI) and the Basic Quality (BQ-System). Both rock mass classifications were then correlated to the Rock Mass Rating (RMR) for the tunnel support system determination. Another support system determination based on the Japanese Society of Civil Engineers (JSCE, 2007) method was also compared. The result showed that the rock masses at the tunnel elevation had very poor to poor quality according to GSI, RMR, and BQ. The rock masses were classified as category class E and DII according to the JSCE competence factor. The recommended tunnel support system based on the RMR are shotcrete, rockbolt, steel set, while those based on the JSCE are shotcrete, rockbolt, steel support, and lining. This paper is expected to provide a better understanding of tunnel construction in weak rock masses, particularly in Indonesia.